APLIKASI ANALISIS KORESPONDENSI UNTUK MELIHAT PERKEMBANGAN PEMBANGUNAN WILAYAH DI KABUPATEN SUMEDANG - Sudartianto Sudartianto Sudartianto (JURNAL ISTEK, 2011)
In this paper reviewed the development progress in the district through the analysis corespondence Sumedang. Development indicators used consisted of large educational facilities, large trading companies and peson income families per day. Based on the analysis results obtained corespondence conclusion that the sub-districts that have passed provincial roads educational facilities compared to most sub-districts that are not provincial roads impassable.